Kesulitan Belajar dan Faktor-faktor yang Mempengaruhi Kesulitan Belajar - Armella, Rega; Rifdah, Khonsaullabibah Maisun Nur (Sultan Idris Journal of Psychology and Education, 2022)
This study aimed to identify and describe learning difficulties in children with various factors that cause learning difficulties. The research uses a qualitative approach with literature studies from books and journal articles. The results of the study found the interaction of learning difficulties as various disorders, both disorders in listening, reading, writing, and listening, caused by various factors such as internal and external. Learning difficulties are divided into two broad categories, namely developmental and academic learning difficulties. Factors of learning difficulties in children are the disruption of brain function, heredity factors, and environmental and nutritional factors. Meanwhile, if viewed from the phenomenon of learning difficulties based on the learning process, the factors that influence it are internal factors that come from within the child or student. External factors related to conditions from outside the child or student. In controlling learning difficulties, it is necessary to carry out comprehensive handling, which can be done in the medical and educational fields. Various significant figures have difficulty learning; one of them is Albert Einstein.